Systemizing the Management of University-Industry Collaboration: Assessment and Roadmapping - Nathasit Gerdsri (2022)
Many firms increasingly collaborate with universities to create innovation through the commercialization of scientific knowledge. However, a variety of mismatches between a firm's interests and the value delivered by university partners (e.g., common knowledge base, strategic goals, agreements on intellectual property management, etc.) can cause rough interactions and relationships. Therefore, managers demand an effective practice to support the management of university-industry collaborations (UICs). This article builds on the previous work on a matching quality assessment model by extending its applicability to propose an analytical framework for developing a strategic roadmap to guide relationship development toward effective UIC.